Sistem Informasi Salon Kecantikan Dan Perawatan Studi Kasus Pada Salon Griya Poetri - Wiyanto Wiyanto (Jurnal SIGMA, 2021)
Griya Poetri, office located at Permata No. 20 Jl. Azalia Raya Green Valley Lippo Cikarang, a business in the beauty salon and treatment for men and women which include cutting, blow, straight iron, curly iron, bun, smoothing, perming, rebonding, coloring, highlights, bleacing, cream bath, makeup, pedicure, manicure, hand massage, foot reflexi etc. Griya Poetri require administrative system and the right information, quickly, accurately and efficiently, which can adopt administrative difficulties in terms of covering existing transactions and income statement in accordance with the wishes of the owner of a beauty salon and treatment Griya Poetri. So the system created can be used in accordance with the needs of the organization. Keyword: Information Systems, Administration